Women and Violence: An Analysis of Violence Against Women in Damar Siput Plantations During the Martial Law (2003-2004) - Sabita, Al Mukaramah (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
The conflict during the Military Emergency period that occurred throughout 2003-2004, affected women workers at PT Damar Siput. Thus, this research aims to examine: what was the situation of the Damar Siput plantation during the Military Emergency period so that it was vulnerable to causing violence against women workers on the Damar Siput plantation and the forms of violence. The method used in this research is a historical method which consists of four stages, namely: heuristics, source criticism, interpretation, and writing (historiography). Based on the research results, it is concluded as follows. 1) The Damar Siput Plantation, which initially ran smoothly, experienced a situation after the implementation of Military Emergency, this situation caused a lot of pressure and violence which was predominantly experienced by female workers. This pressure and violence was carried out by GAM and the army/officials. 2) The forms of violence experienced by workers at the Damar Siput plantation are divided into two, namely, physical violence and psychological violence. Forms of physical violence include beatings and torture/mistreatment. Meanwhile, psychological violence takes the form of threats, taking hostages and killing family members.